A Pilot Double Blind Randomized Placebo Controlled Trial of a Prototype Computer-Based Cognitive Behavioural Therapy Program for Adolescents with Symptoms of Depression. Issue 4 (July 2014) - Stasiak, Karolina; Hatcher, Simon; Frampton, Christopher; Merry, Sally N.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Depressive disorder is common in adolescents and largely untreated. Computers offer a way of increasing access to care. Computerized therapy is effective for depressed adults but to date little has been done for depressed adolescents. Aims: The objective of this study was to examine the feasibility, acceptability, and effects of The Journey, a computerized cognitive behavioural therapy (cCBT) program for depressed adolescents. Method: Thirty-four adolescents (mean age 15.2 years, SD = 1.5) referred by school counsellors were randomly assigned to either cCBT or a computer-administered attention placebo program with psychoeducational content (CPE). Participants completed the intervention at school. Data were collected at baseline, post-intervention and at a 1-month follow-up. The primary outcome measure was the Child Depression Rating Scale Revised (CDRS-R); secondary outcome measures were: RADS-2; Pediatric Quality of Life Inventory; Adolescent Coping Scale (short form); response and remission rates on CDRS-R. Completion rates and self-reported satisfaction ratings were used to assess feasibility and acceptabililty of the intervention. Results: Ninety-four percent of cCBT and 82% of CPE participants completed the intervention. Eighty-nine percent liked The Journey a lot or thought it was "okay" and 89% of them would recommend it for use with others as is or after some improvement. Adolescents treated with cCBT showed greater symptom improvement on CDRS-R than those treated with CPE program (mean change on cCBT = 17.6, CI = 14.13–21.00; CPE = 6.06, CI = 2.01–10.02; p< .001). Conclusions: It is feasible, acceptable and efficacious to deliver computerized CBT to depressed adolescents in a school setting. Generalizability is limited by the size of the study.